EFFECTIVENESS OF HORMONAL TREATMENT IN PATIENTS WITH COMBINED ENDOMETRIAL PATHOLOGY AND BENIGN FORMATIONS OF MAMMARY GLANDS - Yu. S. Shapoval (Сучасні медичні технології)
Issues related to the treatment of HPE are still very relevant, which is due to the high frequency of relapses of this disease. Today, in the arsenal of modern medicine, there are various approaches to the treatment of HPE. However, the development of benign neoplasms of the mammary glands against the background of HPE limits the possibilities of conservative treatment. Hormonal therapy remains one of the most common methods of treating HPE.